2011
DOI: 10.1007/s00268-011-1209-1
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Indication of Parotidectomy Using the Modified Facelift Incision in Benign Lesions: Retrospective Analysis of a Single Institution

Abstract: The modified facelift incision is feasible for most benign parotid lesions regardless of tumor location, even for anterior or superior tumors. Using the modified facelift incision may be extended with a surgeon's accumulated experience, but for a large deep-lobe tumor, the modified Blair incision is still considered useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 35 publications
1
59
0
Order By: Relevance
“…Temporary changes to facial movements may happen in between 10% and 70% of cases (Hegazy et al, 2011), andLee et al, (2011) did not observe differences between the incidence of facial paralysis in patients undergoing parotidectomy by the modified facelift incision or the classic Blair approach. Contrary to this, Wasson et al (2010) found a 34% of facial nerve dysfunction in patients operated via the Blair incision, compared to 20% in the cases approached through a modified facelift.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 85%
See 3 more Smart Citations
“…Temporary changes to facial movements may happen in between 10% and 70% of cases (Hegazy et al, 2011), andLee et al, (2011) did not observe differences between the incidence of facial paralysis in patients undergoing parotidectomy by the modified facelift incision or the classic Blair approach. Contrary to this, Wasson et al (2010) found a 34% of facial nerve dysfunction in patients operated via the Blair incision, compared to 20% in the cases approached through a modified facelift.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 85%
“…Most extirpative surgeons still opt for traditional approaches such as the Blair incision, which are effective from an oncologic standpoint, but not ideal from an aesthetic point of view. In searching for a more aesthetically pleasing scar after parotidectomy, surgeons have tried various approaches (Terris et al, 1994;Lee et al, 2011). One of them is the modified facelift incision, which has gained increasing popularity for its cosmetic benefits; however, several authors (Upile et al, 2010) advise that this approach may not be suitable for all parotid tumors, especially those located in the periphery of the parotid gland or in cases of deep lobe tumors where wide access is required to avoid tumor rupture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The size and location of the mass must be taken into account to ensure adequate access, in order to achieve complete excision. 7,8 In children, the recurrence rate for pleomorphic adenoma is 20 per cent, compared with 1 to 9 per cent in adults. 4 This means that the planning and execution of surgery need to be done by an experienced surgeon who operates on similar cases on a regular basis.…”
Section: Discussionmentioning
confidence: 98%